Polymerase chain reaction optimization and polymerase chain reaction-restriction fragment length polymorphism of ambal riong (Solen sarawakensis) from bay area - Florence, Laiping (Universiti Malaysia Sarawak, UNIMAS, 2007)
Solen sarawakensis (Ambal Riong) is one of the razor clam that can be found in Kuching. This project is designed to (i) amplify 16S mtDNA, ITS 1 and ITS genes, (ii) explore the possibility of using PCR-RFLP technique and (iii) find DNA-based genetic markers among individual in this species. This study had successfully established the protocols for amplification of the selected genes. The amplification of 16S mtDNA, ITS 1 and ITS genes using PCR technique yielded the fragment of 500bp, ≈500bp and ≈1100bp, respectively. The 16S mtDNA was later sequenced and cloned. The resulted sequence was 500bp in size. The cloned procedure had also yielded positive result. More than 1000 white colonies were observed on IPTG/Amp/X-Gal LB plate. However, further analysis could not be done due to time constraint. In this study, 7 restriction enzymes (BamHI, BstZI, MspI, AluI, Csp61, HindIII and HaeIII) were selected. Only enzymes AluI and Csp61 give the restriction profiles in the PCR-RFLP analysis on 16S mtDNA gene. For ITS 1, 4 enzymes (AluI, Csp61, HindIII and HaeIII) successfully cut the ITS 1 fragment. PCR-RFLP analysis on ITS gene using selected restriction enzymes showed that Csp61, MspI, HaeIII and HindIII cut the fragment.